Lysosome-targeted carbon dots for ratiometric imaging of formaldehyde in living cells. Issue 17 (17th April 2019) - Liu, Haifang; Sun, Yuanqiang; Li, Zhaohui; Yang, Jie; Aryee, Aaron Albert; Qu, Lingbo; Du, Dan; Lin, Yuehe
Abstract : CDs based ratiometric fluorescent probe for formaldehyde was developed and successfully employed in bioimaging of formaldehyde in lysosome. Abstract : Formaldehyde (FA) is involved in many biological processes and is closely connected with many diseases including Alzheimer's disease and cancer. Therefore, methods for sensitive and selective detection of FA in living cells are highly demanded. As a new class of carbon nanomaterials, carbon dots (CDs) have attracted great attention owing to their robust photostability, good biocompatibility and environmental friendliness. In this manuscript, the first lysosome-targeted CDs for ratiometric fluorescence detection of FA were efficiently prepared from dexamethasone and 1, 2, 4, 5-tetraaminobenzene through the microwave-assisted hydrothermal method. These CDs show highly selective and sensitive sensing ability towards FA with fast response and great changes of ratio values. The CDs exhibit robust photostability and good biocompatibility and were successfully employed in ratiometric fluorescence bioimaging of FA fluctuations in lysosomes of living cells, which demonstrates their great practicability in FA-related bioanalysis and biological studies.